2017
DOI: 10.1002/cphc.201701086
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Distribution and Speciation of Boron and Cesium in BCsX Zeolite Catalysts for Styrene Production

Abstract: An improved understanding of the nature and distribution of boron and cesium species in BCsX zeolites is a prerequisite to guide future developments in the environmentally attractive, yet challenging, production of styrene through the side-chain alkylation of toluene with methanol. Herein, standard characterization and catalytic tests are complemented by integrated visualization through time-of-flight secondary-ion mass spectrometry and energy-dispersive X-ray spectroscopy and detailed assessment by Cs and B N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal,, whereas tetrahedral boron geometry is recovered upon hydration . Such weaker Brønsted acidity of B‐sites guarantees a high selectivity for ethylene from methane and is relevant for the environmentally friendly production of styrene . Aluminophosphates (ALPO), generally have neutral framework and large pore sizes, like in VPI‐5.…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal,, whereas tetrahedral boron geometry is recovered upon hydration . Such weaker Brønsted acidity of B‐sites guarantees a high selectivity for ethylene from methane and is relevant for the environmentally friendly production of styrene . Aluminophosphates (ALPO), generally have neutral framework and large pore sizes, like in VPI‐5.…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…Styrene is a key building‐block chemical for the production of polymers with significant application value . Producing styrene by side‐chain alkylation of toluene with methanol was deemed as a sustainable one‐step alternative to the present two‐step route via the alkylation of benzene with ethylene and sequential hydrogenation of the ethylbenzene product …”
Section: Methodsmentioning
confidence: 99%
“…It has been most frequently studied as a base catalyst and various modifications were made to improve its activity and selectivity for styrene . Up to now, the modification of CsX has been mainly concentrated on introducing boron containing compounds and alkali metal oxides ,,…”
Section: Methodsmentioning
confidence: 99%
“…1 Since then, this reaction has attracted widespread attention and was deemed as a sustainable one-step alternative for the current two-step route through the alkylation of benzene with ethylene and sequential dehydrogenation of the ethylbenzene product. 2,3 In spite of many studies in the past decades, there are still lots of unsolved problems, among which the relatively low catalytic conversion of reactants is the most urgent one as it is the main restriction for realizing industrial application of this potential and sustainable technology.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] According to a current consensus, cesium ion exchanged zeolite X (CsX) is the most promising catalyst for side-chain alkylation of toluene with methanol. 2,4,13 It was found that further modifying CsX with cesium oxide can greatly improve its catalytic activity for side-chain alkylation of toluene with methanol. 5,8,14,15 Archier et al found that modifying CsX with cesium oxides can promote the side-chain alkylation of toluene with methanol, and suggested it was attributed to the promotion for the generation of formaldehyde from methanol on the alkali oxides particles.…”
Section: Introductionmentioning
confidence: 99%